Spall damage in single crystal tin under shock wave loading: A molecular dynamics simulation. (September 2021) - Wang, Xin-Xin; He, An-Min; Zhou, Ting-Ting; Wang, Pei
Abstract: Using molecular dynamics methods, we investigated the spall damage in single crystal tin under different shock pressures. The results show that release melting and shock melting occur when the shock velocities increase in the metallic tin. The spall strengths in the molten tin are ~1.5–2.0 GPa lower than that in solid. When release melting occurs, the spall strength drops rapidly, whereas the downtrend of the spall strength becomes gentle during shock melting. The results also show that the spall strength is affected by not only the shock pressure and phase state, but also the temperature and strain rate. By visualizing the development of spall damage, we find that it forms a spall layer in the solid. In molten tin, a cavitation region with a large volume is formed. The maximum number of voids increases with an increase in the shock pressure. The growth rate of the void volume fraction slows down after reaching the initial time of void growth at different impact pressures. We elucidated the variation trend of spall strength between solid and molten tin under different shock pressures. The relevant results can provide a reference for future studies on spall damage investigations. Highlights: The spall strengths in the molten tin are ~1.5–2.0 GPa lower than that in solid. The spall strength drops rapidly when release melting occurs, whereas the downtrend becomes gentle during shock melting. The spall strength is affected by the shock pressure and phase state.